Usos y costumbres del pueblo pijao vistos desde la interculturalidad como una alternativa pedagógica en las ciencias sociales: análisis de la producción bibliográfica colombiana entre 1991 y 2023 - Viuche Girón, Darwin Rosed (Universidad Antonio Nariño, 2024)
The present degree work is a systematic review of the academic roblemaa aimed at the documentary roblema of the uses and customs of the Pijao people, from the intercultural perspective as a pedagogical commitment in the social sciences. From the review of degree theses, magazine articles and books with a time frame between 1991 and 2023. In this way, a synthesis of the texts found was made to form the exposed document, which is made up of three essential pillars: A. Interculturality, B. Uses and customs and C. Social sciences, to answer our research roblema.